Economic Analysis of Lapsi (Choerospondias axillaris Roxb.) Production in Parbat District, Nepal - Paudel, P.; Neupane, S.; Adhikari, P.; Tiwari, U. (Journal of the Institute of Agriculture and Animal Science, 2020)
A survey-based study was conducted to assess the production scenario of Lapsi in Falewash, Parbat. Purposively selected twenty-four Lapsi entrepreneurs in Falewash Municipality, Parbat district were interviewed with a well-structured questionnaire that explored Lapsi production data in the last twelve years, which were then processed and analysed with descriptive statistics using computer software MS-Excel 2010. The average landholding size of the respondent farm households was 17.6 Ropani (0.88 ha), and 1 8% of the land was occupied by Lapsi. However, 95% of the Lapsi orchard is established in Pakho/Bari (Upland). A majority (66.7%) of the Lapsi growers were trained either for cultivation, grafting and/or processing techniques. The Lapsi productivity in Falewash, Parbat (12.7 Mt/ha) is above the national average (8 Mt/ha). A Lapsi orchard in Falewash, Parbat can be established with investing NRs. 3,762.89 per Ropani. The average annual operating cost of Lapsi orchard is NRs. 2,052.19 per Ropani, whereas the average annual gross return is NRs.15,890.57 per Ropani. The benefit-cost ratio (BCR) of 2.84, net present value (NPV) of NRs. 30,146.3 and internal rate of return (IRR) of 33% signify the economic importance of Lapsi production. Pay-Back period of eight years in Lapsi production enterprise requires a long-term plan to be established as a cash-generating enterprise. The major problems in the Lapsi production are harvesting difficulty and damage by wild animals (mostly monkeys) whereas the poor transportation facility and inadequate market information are the major marketing constraints.